Tensile and shear behavior of box connector for precast concrete shear walls. (15th October 2021) - Zhou, Yun; Zhang, Baozheng; Hwang, Hyeon-Jong; Xi, Shuhang; Fang, Liang; Huang, Yuan; Yi, Weijian
Highlights: A pair of innovative steel sleeve and box connections were proposed for fully assembled PC shear walls. Pull-out tests for steel sleeve and box connections. Monotonic and cyclic lateral loading tests for PC wall-ground beam joints. An optimized connection was suggested to improve the structural performance of the wall joint. Abstract: As precast concrete (PC) shear walls have been widely used in housing industrialization, reliable connections are important to ensure structural integrity of prefabricated shear walls. In the present study, a pair of innovative steel sleeve and box connections were proposed for rapid installation of fully assembled PC shear walls. Pull-out tests were performed on six PC specimens with sleeve and box connectors. Further, monotonic and cyclic lateral loading tests were performed on eight PC wall-ground beam joints. The test parameters were the configuration of connectors in the pull-out tests, and screw bolt strength, axial compression ratio (ACR), and loading type in the lateral loading tests. The test results showed that early pull-out failure occurred in the embedded sleeve due to flexural deformation of the horizontal pin rod, while fracture of the screw bolt occurred in the box component. Shear strength of the wall joint was developed by adhesive/interlock action, dowel action, and shear friction action. As screw bolt strength and ACR increased, the shear strength increased. To investigate the characteristic failure behavior of the connector and wall joint specimens, nonlinear finite element analysis (FEA) was conducted using ABAQUS program. A parametric study was performed to investigate the effect of design parameters on the pull-out and shear strength of the wall joint. Further, the test results were compared with the current design code requirements. Finally, an improved connection was suggested to increase the structural performance of the wall joint.